Between Affect and Interaction: A Thematic Literature Review on the Determinants of Children's Social-Emotional Development - Ashar Ashar; Reski Idamayanti (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study investigates factors influencing early childhood social-emotional development through a thematic literature review of 25 recent scholarly sources published between 2018 and 2025. A systematic search was conducted across major academic databases, including Google Scholar, ERIC, Elsevier, MDPI, Sage Journals, and Taylor Francis. The collected studies were analyzed using thematic synthesis to identify recurring patterns and key determinants. The results reveal four principal categories affecting social-emotional development: (1) internal affective factors, (2) external social interaction factors, (3) contextual and environmental influences, and (4) the integration of affective and interactive dimensions. The findings indicate that children’s social-emotional development is shaped not only by individual characteristics but also significantly by the quality of interactions with caregivers, peers, and the broader learning environment. In particular, supportive and responsive relationships emerge as critical components in fostering emotional regulation and social competence. The study concludes that a holistic approach, integrating both affective and social interactional aspects, is essential for optimizing early childhood development. These findings have important implications for educational practice and policy, highlighting the need for contextualized, evidence-based social-emotional learning models that are responsive to children’s developmental needs.